Usefulness of computed tomography for hospitalized adult patients with fever to investigate cause of fever: single-center, retrospective cohort study - Hamabe, Fumiko (Jpn J Radiol, 2021)
PURPOSE: To verify that physicians’ presumptive diagnosis is the most significant factor for finding any signs related to the cause of fever on computed tomography (CT) images. MATERIALS AND METHODS: This single-center retrospective cohort study included patients (age ≥ 16 years) who underwent CT to investigate the cause of fever between January 1, 2014, and August 31, 2016. Patients who underwent surgical procedures were excluded. The primary outcome was the presence of suspicious CT findings related to the cause of fever. We performed univariate and multivariate logistic regression analyses, adjusted for CT contrast agent use, quick sequential organ failure assessment score > 1, and C-reactive protein level. RESULTS: We enrolled 171 patients, of which 57 had CT findings, and 114 did not. Multivariate logistic regression analyses demonstrated a significant difference for the presence of a presumptive diagnosis by the attending physician (odds ratio, 4.99; 95% confidence interval 2.31–10.76; p < 0.01), but not for other covariates, including C-reactive protein. CONCLUSIONS: In hospitalized patients with fever, an attending physicians’ presumptive diagnosis is associated with the presence of fever-related CT findings. Improving the quality of the diagnostic assessment before the CT scan may lead to more appropriate CT imaging use. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s11604-021-01117-5.